Development and Evaluation of an Attendance Tracking System Using Smartphones with GPS and NFC. Issue 1 (31st December 2022) - Chiang, Te-Wei; Yang, Cheng-Ying; Chiou, Gwo-Jen; Lin, Frank Yeong-Sung; Lin, Yi-Nan; Shen, Victor R. L.; Juang, Tony Tong-Ying; Lin, Chia-Yang
ABSTRACT: As usual, if many students are attending the lectures, their attendance tracking may become time consuming. Furthermore, there are some possibilities that students could cheat the lecturers of their attendance in the classroom. Therefore, a reliable method to manage the attendance tracking has become a critical issue. This paper aims to propose an attendance tracking system using an Android smartphone equipped with Global Positioning System (GPS) and Near Field Communication (NFC) technologies. Lecturers and students can constantly connect with one another by using smartphones to check and show their attendance automatically if they download and install the software Application (App). Finally, the experimental results have shown that our proposed system can successfully reduce some time for tracking students' attendance. It also allows users to use their own Android smartphones without purchasing other electronic devices.